Continuous reduction of nickel and cobalt from ammoniacal sulfate solutions by hydrogen in a tubular reactor / - Elmarghani, Mohamed Abdusalam (My University, 1983)
Ammoniacal nickel sulfate solution treated with ferrous sulfate (nucleating agent) was contacted with hydrogen in a continuous countercurrent tubular reactor. Bottom products (liquid-solid) and overflow products (gas-liquid) were separated in individual high pressure separators. Nickel conversion, and ultimately the yield to metallic nickel, were found to depend on: reactor temperature, pressure, residence time, pH, excess hydrogen input and concentrations of ferrous and ammonium sulfates in feed solution. With 25% excess hydrogen, 3580 Kpa and a residence time of 5 minutes, 90 percent yield was obtained at 193(DEGREES)C in a single pass. Several experiments were made to find a suitable nucleating agent for cobalt reduction. The results indicated that colloidal graphite as well as the mixture of sodium sulfide-potassium cyanide nucleated cobalt in 5 minutes of residence time under the conditions of 3580 to 5753 Kpa and 220(DEGREES)C. For essentially complete conversion and 90 percent yield in a single pass, longer residence times (20-30 minutes) were required under the above conditions of temperature and pressure.
Keywords: Engineering, Metallurgy.